2001
DOI: 10.1007/s00464-001-0032-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic myotomy vs endoscopic dilation in the treatment of achalasia

Abstract: Laparoscopic myotomy is as save and effective as endoscopic dilation in the treatment of achalasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Two randomized studies [23,24] compared the efficacy of pneumatic dilation with laparoscopic myotomy in patients with achalasia. Our meta-analysis showed that there were We used the Jadad scale to assess the quality of trial.…”
Section: Pneumatic Dilation Versus Laparoscopic Myotomymentioning
confidence: 99%
“…Two randomized studies [23,24] compared the efficacy of pneumatic dilation with laparoscopic myotomy in patients with achalasia. Our meta-analysis showed that there were We used the Jadad scale to assess the quality of trial.…”
Section: Pneumatic Dilation Versus Laparoscopic Myotomymentioning
confidence: 99%
“…Thus, it is well documented in comparative studies that the reduction of postinterventional LES pressure is almost twice as high after HM compared to EBD or EBTI [1,13,15,16]. This results in a more efficient reduction in esophageal outflow obstruction and, subsequently, a better esophageal clearance by gravity.…”
Section: Discussionmentioning
confidence: 79%
“…Currently modified such that only an anterior myotomy is performed. Excellent results with cardiomyotomy can be achieved in 90% to 95% of patients [3,6,8,9,26,[30][31][32]34,37,38,[52][53][54][55][56]. It provides more reliable relief of dysphagia than pneumatic dilation as it allows accurate division of LES muscle fibers rather than blind disruption [8].…”
Section: Endoscopic Botulinum Toxinmentioning
confidence: 99%